2021
DOI: 10.1007/s12630-021-02049-4
|View full text |Cite
|
Sign up to set email alerts
|

An environmental scan of visitation policies in Canadian intensive care units during the first wave of the COVID-19 pandemic

Abstract: Purpose In response to the rapid spread of SARS-CoV-2, hospitals in Canada enacted temporary visitor restrictions to limit the spread of COVID-19 and preserve personal protective equipment supplies. This study describes the extent, variation, and fluctuation of Canadian adult intensive care unit (ICU) visitation policies before and during the first wave of the COVID-19 pandemic. Methods We conducted an environmental scan of Canadian hospital visitation policies througho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
32
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 32 publications
1
32
0
1
Order By: Relevance
“…A recent environmental scan of Canadian adult intensive care unit (ICU) visitation policies during the first wave of COVID-19 revealed that 86% of hospitals altered their policies to prohibit or restrict visitors. 1 The restrictive visitation policies were designed to limit the spread of SARS-CoV-2 and to protect the healthcare workforce in the face of uncertainty, yet often neglected the important role of essential care partners. Meanwhile, fear of infection, elevated workloads, and emotional exhaustion caused stress for healthcare providers.…”
mentioning
confidence: 99%
“…A recent environmental scan of Canadian adult intensive care unit (ICU) visitation policies during the first wave of COVID-19 revealed that 86% of hospitals altered their policies to prohibit or restrict visitors. 1 The restrictive visitation policies were designed to limit the spread of SARS-CoV-2 and to protect the healthcare workforce in the face of uncertainty, yet often neglected the important role of essential care partners. Meanwhile, fear of infection, elevated workloads, and emotional exhaustion caused stress for healthcare providers.…”
mentioning
confidence: 99%
“…With the vaccination rate increasing, existing consensus statements will need to be revisited and revised based on emerging evidence of risk and transmissibility to inform visitation policies that consider a visitor’s vaccination status. Sixth, the generalizability of these findings is limited to setting such as Canada where, pre-pandemic, most ICUs had open visitation (24 hr) ( 4 ) and, as such, may not be applicable to jurisdictions with restricted/limited visitation. Future work is needed to understand the barriers to the implementation and facilitators/barriers of adoption of these evidence-informed consensus statements and their sustained uptake during the current and future pandemics.…”
Section: Discussionmentioning
confidence: 98%
“…Patient- and family-centered care (PFCC) is an essential component of high-quality critical care medicine ( 1 ). In response to the increasing number of patients with coronavirus disease 2019 (COVID-19) infection and limited knowledge regarding viral transmission, hospitals enacted strict visitation restrictions to mitigate potential spread of COVID-19 and preserve personal protective equipment ( 2 4 ). These restricted visitation policies prohibited the presence of family members for all hospitalized patients, including ICUs, with limited exceptions (e.g., end-of-life) ( 4 ).…”
mentioning
confidence: 99%
“…présentent les résultats de leur étude de milieu qui décrit l'ampleur, les variations et les fluctuations des restrictions relatives aux visites aux unités de soins intensifs pour adultes au Canada avant (pré-COVID) et à deux points de temps (mid-COVID et COVID-tardif) au cours de la première vague de la pandémie de COVID-19 au Canada. 3 Sur la base de 257 documents décrivant les politiques de visite de 230 hôpitaux/USI canadiens, les auteurs rapportent qu'avant la COVID, plus des deux tiers des USI autorisaient les visites « libres » (24 heures sur 24). Sans surprise, aucun hôpital n'a maintenu les visites libres pendant la pandémie, la majorité adoptant une politique de « visites interdites » hormis pour des exceptions prédéterminées (mid-COVID : 86 %; COVID-tardif : 76 %).…”
Section: Conséquences Des Politiques De Restriction Des Visites à L'unité De Soins Intensifs Pendant La Pandémie De Covid-19unclassified
“…In this issue of CJA, Fiest et al report the findings of their environmental scan which describes the extent, variations, and fluctuations of Canadian adult ICU visitation restrictions before (preCOVID) and at two timepoints (midCOVID and lateCOVID) during the first wave of the COVID-19 pandemic in Canada. 3 Based on 257 visitation policy documents from 230 Canadian hospitals/ ICUs, they report that preCOVID, over twothirds of ICUs permitted ''open'' (24-hr) visitation. Unsurprisingly, none of the hospitals retained open visitation during the pandemic, with the majority adopting a ''no visitor'' policy with pre-specified exceptions (midCOVID: 86%; lateCOVID: 76%).…”
mentioning
confidence: 99%